Manajemen Kepala Sekolah Dalam Mengintegrasikan Nilai Nilai Pendidikan Karakter Pada Siswa SD Negeri 46 Kota Banda Aceh - Bararah, Isnawardatul (Intelektualita: Journal of Education Sciences and Teacher Training, 2025)
This study aims to analyze how the principal manages the integration of character education values in SD Negeri 46 Banda Aceh. The method used in this study is a qualitative approach, with data collection through observation, interviews, and documentation. The results of the study indicate that the principal at SD Negeri 46 applies a comprehensive management strategy, involving the entire school community, including teachers, students, and parents, in the character development process. Extracurricular programs and social activities held at the school serve as a means to instill positive values, such as discipline, responsibility, and cooperation. In addition, continuous evaluation of the character education program is carried out to ensure the effectiveness and relevance of the activities implemented. The results of the study in the school show that: the principal's management has been running effectively, this can be seen from the principal's habits in creating a learning environment that supports the development of student character, which produces a superior generation in academic aspects. This study is expected to provide a significant contribution to the development of character education management practices in other elementary schools, while still upholding integrity and strong moral value